A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 6 TAMBUSAI IN COMPREHENDING DESCRIPTIVE READING TEXTS - Fauzan, Andriko; Jismulatif, Jismulatif; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is aimed to find out the reading ability of the second year students of SMPN 6 Tambusai. The population of this research is the second year students of SMPN 6 Tambusai. The number of sample is 30 students selected by using cluster random sampling technique. The instrument to collect the data was multiple choice test items with 30 questions. . Each text consist of 6 questions which cover the components of reading and the components of descriptive that is finding main ideas, finding restatements, finding meaning of difficult words, finding references, finding factual informations, and finding social functions. The data were analyzed by classifying them into five levels of mastery, such as excellent, good, avarage, poor, and very poor. Based on the findings this research, it was found that the students’ reading ability of the first year students of SMPN 6 Tambusai was in good level with the mean score was 62.05. The implication of this research is that the second year students of SMPN 6 Tambusai have a good ability in reading descriptive text.Key Words: Students’ ability, Reading, Descriptive Text